2015
DOI: 10.1089/scd.2015.0107
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Bone Marrow Mononuclear Cells Exert Broad Effects on Short- and Long-Term Biological and Functional Outcomes in Rodents with Intracerebral Hemorrhage

Abstract: Autologous bone marrow-derived mononuclear cells (MNCs) are a potential therapy for ischemic stroke. However, the effect of MNCs in intracerebral hemorrhage (ICH) has not been fully studied. In this study, we investigated the effects of autologous MNCs in experimental ICH. ICH was induced by infusion of autologous blood into the left striatum in young and aged male Long Evans rats. Twenty-four hours after ICH, rats were randomized to receive an intravenous administration of autologous MNCs (1 · 10 7 cells/kg) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 63 publications
2
23
0
Order By: Relevance
“…These positive effects on functional outcomes have been replicated in various animal stroke models as well [3]. Similarly, in both injury models, BMMNCs dampen the secondary neuroinflammatory response to injury [4][5][6]. Finally, there appears to be a consistent treatment window of 24-72 hours [7].…”
Section: Introductionmentioning
confidence: 98%
“…These positive effects on functional outcomes have been replicated in various animal stroke models as well [3]. Similarly, in both injury models, BMMNCs dampen the secondary neuroinflammatory response to injury [4][5][6]. Finally, there appears to be a consistent treatment window of 24-72 hours [7].…”
Section: Introductionmentioning
confidence: 98%
“…To improve neurological sequelae after intra-ventricular hemorrhage, many research efforts using stem cells have been carried out in animals (30)(31)(32). Ahn et al performed intra-ventricular transplantation of umbilical cord bloodderived mesenchymal stem cells (MSCs) for induced intraventricular hemorrhage in Newborn Sprague-Dawley rats.…”
Section: Discussionmentioning
confidence: 99%
“…Bolisetty et al showed that infants born at 23 to 28 weeks' gestation with grade III-IV intra-ventricular hemorrhage had high rates of developmental delay (17.5%), cerebral palsy (30%), deafness (8.6%), and blindness (2.2%) (2). According to Pierrat et al, the overall rate of cerebral palsy in infants born at [24][25][26][27][28][29][30][31], and 32-34 weeks of gestation was 6.9, 4.3, and 1%, respectively (14).…”
Section: Introductionmentioning
confidence: 99%
“…A peripheral vein was used for BMMC transplantation, since the procedure could be easily performed without the need of intubation for bronchoscopy. Intravenous administration has demonstrated a good safety profile for delivery of either BMMCs or MSCs in experimental models [6,7,9,[16][17][18][19]. Even though a systemic route was used in the cases described herein, these cells are efficiently delivered to the lungs, as they are subject to a first-pass effect [20].…”
Section: Discussionmentioning
confidence: 99%